(untitled) (Research, Society and Development, 2022)
Purpose: To determine the effect of glass ionomer sealants in preventing occlusal caries on erupting primary molars. Materials and Methods: A longitudinal clinical trial with children 1-3 years old was held in the city of São Luiz do Paraitinga - SP, participants of the "First Smile Project". The experimental design was a split-mouth for 62 healthy primary molars (1º and 2º molars), 31 on control group (C) and 31 on sealant group (S). Supervised toothbrushing was oriented with dentifrice "Oral-B Pro Saúde” (above 1000 ppm Fluoride), prophylaxis and diagnosis by ICDAS. Teeth on (S) group were sealed with glass ionomer. Revaluations for both groups were held after 3, 6, 12 and 18 months (T1, T2, T3 and T4) respectively by ICDAS and ICDAS CARS. The Chi-square test and Cox Regression analysis was used. Results: The results for progression or not of carious lesions (%), respectively, were Group C - T1, 46.8% and 53.2%; T2, 47.2% and 52.8%; T3, 48.5% and 51.5%; T4, 47.8% and 52.2%. Group S - T1, 66.7% and 33.3%; T2, 56.2% and 43.8%; T3, 52.6% and 47.4%; T4, 52.9% and 47.1%. Conclusion: There was no difference between groups on follow-up periods and there was no difference between variables to children and the teeth (p = 0.5), suggesting that the ionomer sealing presented the same preventive effect of the control group.